Autoimmune hemolytic anemia during long‐term administration of nivolumab for metastatic melanoma. Issue 5 (1st May 2021) - Nakajima, Koji; Korekawa, Ayumi; Rokunohe, Daiki; Nakano, Hajime; Sawamura, Daisuke
Abstract : Autoimmune hemolytic anemia secondary to nivolumab occurred in a patient with melanoma.